Pour un nouveau paradigme de la formation des maîtres : des cliniques de l'éducation - Frédérique Marie Prot (Nantes Université, 2017)
Our proposal is in line with the work on the universalization of teacher training. Reflecting on the gap between the concerns of reseachers and professors, Sensevy (2011) proposed in Theory of Join Action in Didactics a new paradigm of training that he designed on the model of medical clinics. The instrument of such clinics would be co-operative didactic engineering developed jointly by researchers and professors, aiming to constitute a science of joint action. This joint development leads us to think of a new model of teacher training as a process of investigating the profession carried out jointly by reseachers and professors in training.